Analisa Kinerja Mesin Roughing Stand dengan Menggunakan Metode Overall Equipment Effectiveness (OEE) dan Failure Mode Effect Analysis (FMEA) - Hasrul, Hasrul; Shofa, M. Jihan; Winarno, Heru (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2017)
The roughing stand machine functions for steel/product formation and the roll has five stands, and from each position has a different turn. In the production process, this machine also experiences obstacles that hinder the process [of production]. This study aims to determine the value of Overall Equipment Effectiveness (OEE) and analysis of the causes of OEE values have not been maximized based on the review of Failure Mode and Effect Analysis (FMEA). The data used are historical data of roughing stand machines during July 2016-December 2016. Based on the data processing performed, the results of the Overall Equipment Effectiveness (OEE) obtained on the Roughing Stand machine purchased at 57.5. The potential failure priority is base on the order of Risk Priority Number (RPN), the screw up non-working item has the most considerable RPN value (56). Regular lubrication is one way to maximize screw up performance..